CardioNVT: an AI platform for immunostaining-free, high-throughput cardiomyocyte ploidy assessment in situ - Zehao Yao; Lina Bai; Zhongkai Luo; Yuan Liu; Lingfang Chen; Minjiong Zhao; Youzhi Sun; Libo Zhang; Yu Nie (Science Bulletin, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Efficient biosorption of molybdenum (VI) using Chlorella pyrenoidosa biomass: Mechanistic insights and sustainable application in water remediation - Zhixin Song; Lingfang Cui; Xunan Li; Zichen Zhang; Chao Zhang; Gangfu Song; Yu Zhao; Wenzhong Tang (Journal of Cleaner Production, 2025)

β-lactam antibiotics vs vancomycin in treating methicillin-sensitive staphylococcus aureus bloodstream infections: a meta-analysis of clinical outcomes - Guoliang Yu; Yonghai Lou; Lingfang He; Zhitao Wang; Yu Ren (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Global temperature behavior monitoring and analysis of a three-tower cable-stayed bridge - Lingfang Li; Yushi Shan; Qiang Jing; Yu Yan; Zili Xia; Yong Xia (Engineering Structures, 2023)

Vibration-based FRP debonding detection using a Q-learning evolutionary algorithm - Zhenghao Ding; Lingfang Li; Xiaoyou Wang; Tao Yu; Yong Xia (Engineering Structures, 2023)

Altered brain activity in the bilateral frontal cortices and neural correlation with cognitive impairment in schizophrenia - Lingfang Yu; Lei Guo; Xinyu Fang; Fuyin Yang; Yan Chen; Yewei Wang; Dandan Wang; Zenan Wu; Ruimei Liu; Xing Tian; Chen Zhang (Brain Imaging and Behavior, 2022)

The effects of lanthanum chloride on proliferation and apoptosis of cervical cancer cells: involvement of let-7a and miR-34a microRNAs - Lingfang Yu; Jieqi Xiong; Ling Guo; Lifang Miao; Sisun Liu; Fei Guo (BioMetals, 2015)